Graphite-high density polyethylene laminated composites with high thermal conductivity made by filament winding - W. Lv; S. Sultana; A. Rohskopf; K. Kalaitzidou; A. Henry (eXPRESS Polymer Letters)
The low thermal conductivity of polymers limits their use in numerous applications, where heat transfer is important. The two primary approaches to overcome this limitation, are to mix in other materials with high thermal conductivity, or mechanically stretch the polymers to increase their intrinsic thermal conductivity. Progress along both of these pathways has been stifled by issues associated with thermal interface resistance and manufacturing scalability respectively. Here, we report a novel polymer composite architecture that is enabled by employing typical composites manufacturing method such as filament winding with the twist that the polymer is in fiber form and the filler in form of sheets. The resulting novel architecture enables accession of the idealized effective medium composite behavior as it minimizes the interfacial resistance. The process results in neat polymer and 50 vol% graphite/polymer plates with thermal conductivity of 42 W·m–1·K–1 (similar to steel) and 130 W·m–1·K–1 respectively.